Anatomia foliar y xilematica de Ochoterenaea colombiana Barkley - Araque, O.Z.=700 1 Gamez A, L.E.
(En, Es)
Ilus., 40 ref.
Keywords: ANACARDIACEAE; ANATOMIA DE LA PLANTA; HOJAS; XILEMA; MEDIO AMBIENTE; VENEZUELA; OCHOTERENAE COLOMBIANA